Ações afirmativas nas ciências médicas: impactos das cotas no curso de Medicina da UFPB à luz dos direitos humanos - Oliveira, José Kellyton Pessoa de (2019)
This paper seeks to contribute to the process of democratization of access to the Medical School of the Federal University of Paraíba (FUP) to under-represented popular segments of groups in this undergraduate degree - low income, black, brown, indigenous people - from affirmative actions institutionally implemented in 2011 (RES. 09/2010 CONSEPE) and strengthened in 2012 by Federal Law No. 12.711 / 2012. The study starts from the idea that Medicine is a course with high social prestige, according to Costa's studies (2017) and, therefore, have always been populated by economically privileged social extracts, which makes it a fertile ground for an investigation of the impacts brought by affirmative actions. The objective is to analyze the changes and reconfigurations caused in the course by the quotas from the analysis of institutional documents, as well as from the student perspective. Specific research objectives are (1) To identify policies or institutional actions for access and / or permanence of population segments benefited by the affirmative policy; (2) investigate actions in the medical course related to ethnic issues; and (3) Investigate socio-ethnic-economic inequalities in medical students. The methodology had a quantitative and qualitative approach, involving document analysis, identification of actions at UFPB and medical school, and application of semi-structured on-line interviews, according to Flick (2009, 241-243), with students and egresses, using the thematic content analysis of Bardin (2016) for data interpretation.